2020
DOI: 10.1186/s40816-020-00231-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based management of acute rhinosinusitis with herbal products

Abstract: Background The overuse of antibiotics for unjustified indications such as the management of acute uncomplicated rhinosinusitis has contributed to the emergence of antibiotic-resistant strains of bacteria and prompted the need for alternative treatments. This review assesses the quality of evidence for the management of acute rhinosinusitis with herbal products, with the goal of positioning them among other treatments and identifying future research directions. The MEDLINE database was searched for randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
4
0
1
Order By: Relevance
“…While antibiotic treatment is common, respiratory infections also respond well to treatment with herbal combinations. A recent review affirmed the growing body of evidence for the effectiveness of herbal products as a treatment of acute rhinosinusitis [ 118 ], which is in line with findings from a real-world study that discussed herbal products as a viable alternative to antibiotics [ 119 ]. In addition, guidelines for acute and chronic cough suggest herbal products for uncomplicated respiratory infections, in combination with delayed prescription of antibiotics, i.e., patients could receive prescriptions for antibiotics with no further consultation, in case an infection persists, ultimately resulting in notably fewer patients who will take antibiotics, compared to a prescription at the first consultation [ 108 ].…”
Section: Treatment Of Respiratory Infections With Herbal Medicinal Pr...supporting
confidence: 56%
“…While antibiotic treatment is common, respiratory infections also respond well to treatment with herbal combinations. A recent review affirmed the growing body of evidence for the effectiveness of herbal products as a treatment of acute rhinosinusitis [ 118 ], which is in line with findings from a real-world study that discussed herbal products as a viable alternative to antibiotics [ 119 ]. In addition, guidelines for acute and chronic cough suggest herbal products for uncomplicated respiratory infections, in combination with delayed prescription of antibiotics, i.e., patients could receive prescriptions for antibiotics with no further consultation, in case an infection persists, ultimately resulting in notably fewer patients who will take antibiotics, compared to a prescription at the first consultation [ 108 ].…”
Section: Treatment Of Respiratory Infections With Herbal Medicinal Pr...supporting
confidence: 56%
“…Besides, they have been reported to exhibit an anti-inflammatory and immune-modulating potential and thus may also be supportive in preventing or attenuating mild to moderate SARS-CoV-2 infections [ 4 6 ]. In this pilot screening study, five herbal medicinal products, marketed for the treatment of respiratory infections [ 5 8 ], were explored for their potential to (i) interfere with the binding of the human angiotensin-converting enzyme 2 (ACE2) receptor with the SARS-CoV-2 spike protein. The ACE2 receptor, which has been found in various organs including type I and II pneumocytes, endothelial cells, oral and nasal mucosa, and also the intestinal tissues, liver, kidney, or brain [ 9 , 10 ], has been identified as the key cellular receptor, facilitating the uptake of the SARS-CoV-2 virus into the host cell [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors found positive results approaching significance for BNO 1016 treatment in the reduction of sick leave >7 days in acute upper and lower respiratory tract infections (OR 0.84 [0.7-1.0], p=0.054) [27]. A recent review comparing the existing evidence of different herbal medicinal products in relation to N-acetylcysteine and mometasone furoate nasal spray highlighted the evidence for BNO 1016 in the treatment of ARS [28].…”
Section: Discussionmentioning
confidence: 99%